1992
DOI: 10.1007/bf02191563
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor disturbances in psychiatric patients as a possible basis for new attempts at differential diagnosis and therapy

Abstract: Parts I-III of this series used psychometric assessment of motor performance in psychiatric patients and indicated a "psychotic-motor syndrome" (PMS) in schizophrenic and affective psychoses, which was not found in "neurotic"/reactive or healthy persons. Part IV yielded signs of concomitant brain dysfunction in these patients, demonstrated by EEG mapping as well as other (SPECT/PET) neuroimaging methods. Apart from this "basic science" interest into the pathophysiology of endogenous psychoses we engaged in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

1993
1993
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
3
0
3
Order By: Relevance
“…A significant influence on fine motor ability as tested by the MLS, was shown for age, drugs such as alcohol, hormones (androgens), psychiatric illnesses (depression, schizophrenia) and neurological illnesses (Parkinson's disease, dementia) (15)(16)(17)(18)(19)(20)(21). The test was used in several aptitude tests (job, driving license) (15,18,20). In addition, 16 patients and 15 healthy controls were examined by magnetic resonance imaging (MRI) (superconducting 1.5 T unit, Siemens).…”
Section: Methodsmentioning
confidence: 99%
“…A significant influence on fine motor ability as tested by the MLS, was shown for age, drugs such as alcohol, hormones (androgens), psychiatric illnesses (depression, schizophrenia) and neurological illnesses (Parkinson's disease, dementia) (15)(16)(17)(18)(19)(20)(21). The test was used in several aptitude tests (job, driving license) (15,18,20). In addition, 16 patients and 15 healthy controls were examined by magnetic resonance imaging (MRI) (superconducting 1.5 T unit, Siemens).…”
Section: Methodsmentioning
confidence: 99%
“…(voir figure 1, page suivante) Dans l'optique de la réhabilitation en neuropsychiatrie cognitive (au sens d'adaptation ou de restauration des savoir-faire dans la communauté sociale (Halligan et Marshall, 1996 ;Günther et al, 1995 ;Jaeger et Douglas, 1992 ;Rebelle et Lapasset, 1995 ;Lapasset, 2000), il apparaît crucial que psychomotriciens et thérapeutes occupationnels prennent en compte la symptomatologie déficitaire pour au moins cinq raisons majeures :…”
Section: Prémissesunclassified
“…• La chimiothérapie s'avère d'une efficacité limitée pour la réduire, même si l'avènement des neuroleptiques atypiques se révèle un progrès considérable ; • La sévérité des symptômes négatifs (l'anhédonie, l'émousse-ment des affects, l'apathie, l'inattention ou les troubles de l'attention, l'apragmatisme, une capacité insuffisante de réponses aux situations, l'isolement ou le retrait social (David et Cutting, 1994) constitue un mauvais facteur de pronostic et d'évolution plus longue de la maladie (d'Amato et Rochet 1995 ;Andreasen, 2004Andreasen, /2001Andreasen, , 1994Andreasen, , 1989aAndreasen, , b, 1982) ; • De nombreux auteurs leur accordent une position centrale suivant diverses perspectives, pour comprendre et améliorer le sort des patients (Dalery et D'Amato, 1995 ;Flaum et Andreasen, 1995 ;Pine et al, 1997 ;Günther et al, 1995, Chen et al, 1995Brenner, 1989 ;Pomini et al, 1998) ; • Plusieurs études bien documentées ont montré que pauvreté psychomotrice et désorganisation cognitive sont corrélées avec un fonctionnement occupationnel et social réduit, alors que la sévérité du syndrome de distorsion de la réalité ne l'est pas de manière significative (d'Amato et Rochet 1995) ; • Enfin, la constellation de la symptomatologie négative peut jouer un rôle dans : -la constitution, le maintien ou le renforcement de croyances erronées sur soi ou les autres ; -renforcer les sentiments d'ambiguïté sur la réalité que peut éprouver le patient aussi bien que l'équipe soignante en ne permettant plus de faire la part de ce qui relève d'un trouble perceptivo-moteur (dysfonction même d'apparence mineur) d'une construction délirante ( Figure 2, page suivante). Troisièmement, les « signes doux » (Soft Signs) s'opposent aux « signes durs » de la neurologie classique.…”
Section: Prémissesunclassified
See 1 more Smart Citation
“…NeumSxker Universit~itsklinik und Poliklinik ffir Psychiatric des Kindes-uud Jugendalters, D-10098 Berlin tary movements and may be related to severity of illness [7,21,20,30]. GUnther [12] describes motor disturbances in schizophrenics and depressed patients which involve changes in the fine and gross movements of the dominant right-hand and the complex motor coordination of their extremities. Bracha [3] found that in contrast to the controls with equal right-and left-turning movements, schizophrenic patients showed a left-prone circling behaviour.…”
Section: Introductionmentioning
confidence: 98%